2014
DOI: 10.1103/physreve.89.032309
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic particles confined in a modulated channel: Structural transitions tunable by tilting a magnetic field

Abstract: The ground state of colloidal magnetic particles in a modulated channel are investigated as function of the tilt angle of an applied magnetic field. The particles are confined by a parabolic potential in the transversal direction while in the axial direction a periodic substrate potential is present. By using Monte Carlo (MC) simulations, we construct a phase diagram for the different crystal structures as a function of the magnetic field orientation, strength of the modulated potential and the commensurabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…We hope that the results presented here will find direct comparison with previous work, particularly with regards to ions confined in traps [1][2][3][4][5][6][7][8][9] as well as assemblies of magnetic particles in a channels [17]. This work should also be relevant to other systems in which buckling is a key feature: for example localised buckling has recently been observed in experiments involving an expanding (growing) elastic beam pinned to a substrate [18].…”
Section: P-4mentioning
confidence: 72%
“…We hope that the results presented here will find direct comparison with previous work, particularly with regards to ions confined in traps [1][2][3][4][5][6][7][8][9] as well as assemblies of magnetic particles in a channels [17]. This work should also be relevant to other systems in which buckling is a key feature: for example localised buckling has recently been observed in experiments involving an expanding (growing) elastic beam pinned to a substrate [18].…”
Section: P-4mentioning
confidence: 72%
“…Le Doussal et al showed that in a d-dimensional two-layer model, both continuous and sharp dynamical transitions can occur if plasticity between the two layers is allowed [156]. Experimental realizations of systems of interacting particles confined in one to three layers can be achieved for vortices in mesoscopic channels [157], coupled 1D Wigner crystal wires [158], colloidal systems [159], dusty plasmas [160], and ions in line traps [161]. Reichhardt and Reichhardt [162] considered Yukawa repulsively interacting particles in two coupled 1D channels separated by an interchannel distance d in the presence of random pinning.…”
Section: Systems With Few Layersmentioning
confidence: 99%
“…(Lucena et al, 2012;Carvalho et al, 2012;Carvalho et al, 2011) for different damping values (Delfau et al, 2011) and different connement intensities and traps in a monodisperse system of interacting particles (Lucena et al, 2012). Single-file diffusion are also present in nature in many different situations such as diffusion experiments with molecules of zeolite (Meier, 1992), in colloids (Konig, 2005;Wei, 2000), charged macroscopic beads (Coupier et al, 2006) and water through molecular-sized channels in membranes (Hernandez, 1992;Morais-Cabral et al, 2001;Doyle et al, 1998) and for magnetic particles and dipoles (Lucena et al, 2014;Galvan-Moya et al, 2014). In SFD, particles are correlated because particle movement induces other particles to move together.…”
Section: Introductionmentioning
confidence: 99%